Zinc-Mediated Regiodiverse Synthesis of Vinyl Bromide Derivatives and Their in situ Palladium-Catalysed Cross-Coupling Reactions - Miersch, Anne; Kohlmeyer, Corinna; Hilt, Gerhard (Synthesis, 2013)
The synthesis of vinyl bromide derivatives was realised by a zinc-mediated addition of a benzylic bromide to a terminal alkyne. The geometry of the C=C bond is dependent on the amount of zinc powder applied. When 5 mol% of Zn is used, the Z-configured vinyl bromide is generated while with 150 mol% the E-geometry is obtained predominantly. In a three-component one-pot reaction, the in situ generated vinyl bromides were reacted further in a palladium-catalysed Suzuki cross-coupling reaction utilizing aromatic boronic acids to obtain trisubstituted double bonds in good overall yields. The reactions were conducted on a 5–20 mmol scale to visualise that the reactions are also capable of generating larger amounts of products.
Keywords: alkynes; cross coupling; palladium; vinyl bromides; zinc